Teaching Kids to Care about Jewish Problems: A Noddings' Approach. Issue 4 (2nd October 2018) - Jacobs, Benjamin M.
Abstract : Drawing on Noddings' work on religion and education (1993), moral education (2002), and citizenship education (2005 2015), this article contemplates how educators both in public schools and parochial Jewish schools might teach students to care about critical issues confronting the Jewish community historically and contemporarily. Its premise is that the teaching of the Jewish experience is presently deficient in both school settings. The article suggests ways that Noddings' conceptions of caring (1992), pedagogical neutrality (1993), and critical lessons (2006) can be adapted and applied to the teaching of Jewish civilization in more appropriate, holistic, and nuanced ways. Its implications are applicable to many other American subgroups whose treatment in the social studies curriculum is typically inadequate.